1999
DOI: 10.1042/bj3420057
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of murine liver phosphatidylserine synthase (PSS)-2: differential regulation of phospholipid metabolism by PSS1 and PSS2

Abstract: Phosphatidylserine (PtdSer) is synthesized in mammalian cells by two base-exchange enzymes: PtdSer synthase (PSS)-1 primarily uses phosphatidylcholine as a substrate for exchange with serine, whereas PSS2 uses phosphatidylethanolamine (PtdEtn). We previously expressed murine PSS1 in McArdle hepatoma cells. The activity of PSS1 in vitro and the synthesis of PtdSer and PtdSer-derived PtdEtn were increased, whereas PtdEtn synthesis from the CDP-ethanolamine pathway was inhibited [Stone, Cui and Vance (1998) J. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 19 publications
(35 reference statements)
0
26
0
1
Order By: Relevance
“…Only the cells enriched with DHA in a serine depleted condition showed inhibited PS accumulation in agreement with the serine requirement for the mammalian PS synthesis using the serine-base exchange reaction. Similarly, over-expressing pss1 and pss2 genes cloned from the liver (Stone and Vance, 1999;Sturbois-Balcerzak et al, 2001) in non-neuronal cells did not increase the PS accumulation (Guo et al, 2007). These data suggest that PS levels are tightly regulated in living cells and these highly unsaturated very long chain fatty acids are uniquely capable of expanding the PS pool specifically in neuronal cells.…”
Section: Regulation Of Phosphatidylserine Accumulation In Cultured Cellsmentioning
confidence: 71%
“…Only the cells enriched with DHA in a serine depleted condition showed inhibited PS accumulation in agreement with the serine requirement for the mammalian PS synthesis using the serine-base exchange reaction. Similarly, over-expressing pss1 and pss2 genes cloned from the liver (Stone and Vance, 1999;Sturbois-Balcerzak et al, 2001) in non-neuronal cells did not increase the PS accumulation (Guo et al, 2007). These data suggest that PS levels are tightly regulated in living cells and these highly unsaturated very long chain fatty acids are uniquely capable of expanding the PS pool specifically in neuronal cells.…”
Section: Regulation Of Phosphatidylserine Accumulation In Cultured Cellsmentioning
confidence: 71%
“…Although little is known about functional domains or the active sites of the mammalian PSSs, several amino acids that are required for serine-exchange activity have been identified [70]. The predicted amino acid sequences of mammalian PSS1 and PSS2 are~30% identical [29,65,66,71] and each PSS appears to contain several membrane-spanning domains. Consistent with these predictions, both mammalian PSS activities are present on microsomal membranes [72][73][74][75][76].…”
Section: The Ps Synthasesmentioning
confidence: 98%
“…Early experiments suggested that PS synthesis is regulated by a phosphorylation reaction involving protein kinase C [78] but more recent studies have not augmented this report. Interestingly, unlike plants in which large amounts of PS accumulate when PSS1 is over-expressed [60], the PS content of mammalian cells appears to be tightly regulated even when the capacity for PS synthesis is increased [65,66]. Over-expression of PSS1 activity in McArdle rat hepatoma cells increased the rate of PS synthesis whereas over-expression of PSS2 did not, suggesting that PSS1, but not PSS2, activity can be rate-limiting for PS synthesis [65,66].…”
Section: Regulation Of Ps Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Two enzymes named PSS1 (PS synthase 1) and PSS2 have been identified for catalyzing the serine exchange reaction in mammalian cells from PC and PE, respectively (Kuge et al 1991Stone et al 1998;Stone and Vance 1999). Because PS, in turn, can be converted to PE by phosphatidylserine decarboxylase (Borkenhagen et al 1961;Voelker 1997;Vance 1998), the PS status in cell membranes is influenced by both PS biosynthesis and PS degradation.…”
Section: Introductionmentioning
confidence: 97%